The Development of a Clinical Nursing Practice Guidelines for The Management of Proper Dosing Interval Times of Intravenous Antibiotics After a Stat Dose - Saengrut, Bumnet; Kanchaiya , Patarapol; Somana , Puttachat; Sutheechai, Sinwisuth; Wongpalee, Tula (Journal of Nurses Association of Thailand Northern Office, 2024)
This research and development study aimed to develop clinical nursing practice guidelines for the management of proper dosing interval times of intravenous antibiotics after a stat dose. This study applied the methods of the National Health and Medical Research Council of Australia. The samples included three groups. The first group was 11 developers of the guidelines. The second group was 30 users of the guidelines. And the third group was 10 clients who received care according to the guidelines. The research instruments used were: 1) the demographic data questionnaires for nurses; 2) the demographic data questionnaires for patients; 3) the guidelines feasibility questionnaires; and 4) the guidelines outcome record form. The study was divided into two phases. Phase1 or R1 was exploring the problems. Phase 2 or D1 was developing the guidelines. Data were analyzed using descriptive statistics, including frequency, percentage, mean, and standard deviation. The results showed that: 1) there were six empirical evidences that passed all criteria.; 2) the developed guidelines consisted of important parts for practice and three tables for administering the second dose of intravenous antibiotics according to drug groups.; 3) the participants considered the very high feasibilities of implementing guidelines in most items.; 4) after implementing the guidelines, 90% of the dosing interval time of intravenous antibiotics was performed at the right time and 90% of the second dose of intravenous antibiotics after a stat dose was given in a proper dosing interval times. Therefore, the developed guideline is effective. Nurses can use it for managing proper dosing interval times of intravenous antibiotics after a stat dose in order to obtain good outcomes for patients with infectious diseases and safety in drug administration.